OSCAR BERMÚDEZ MIRAL: RESEARCHER OF THE NORTE GRANDE, HISTORIAN OF THE NITRATE INDUSTRY, A MAN OF TWO WORLDS. - González Miranda, Sergio (Revista de Historia Social y de las Mentalidades, 2024)
The objective of this article is to do a biographical sketch of the historian Óscar Bermúdez, researcher of the Norte Grande of Chile, especially of the nitrate period. To reach the objective, they played his main works, interviews and analyzed two previous biographical studies about Bermúdez. Nevertheless, the objective of this article is not just to be a character’s biographical sketch, but to establish which will be the main disciplinary and thinking influences in the historiographical work of this researcher. Preferably, the epistemological perspective of Bermúdez is analyzed in which the positivist methodology of his historiographical research is discussed and compared to his narrative technique, especially his published tales where other possibilities are opened to understand this author Ìs thought